1992
DOI: 10.1002/ajpa.1330890102
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphic variation among Finno‐Ugric speaking populations: Methodological alternatives

Abstract: Utilization of dermatoglyphics for population studies is apparently increasing, but methods vary widely among investigators. We investigate how different types of dermatoglyphic data can affect estimates of biological distance among Finno-Ugric speaking populations. Dermatoglyphic distances were calculated using the following categories of traits: 1) Finger ridge-counts (radial and ulnar count for each digit), 2) finger ridge-counts (largest count for each digit), 3) finger pattern types, 4) palm ridge-counts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…These conjectures are supported by Jantz et al (1992) who found that the correlation of phenetic distances with geographic distances were generally low and not significant, with the highest correlation occurring for finger-ridge counts, the lowest with mainline terminations and palm-ridge counts. If there are no correlations between phenetic and geographic distances, one would not expect spatial autocorrelation to be large or significant.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…These conjectures are supported by Jantz et al (1992) who found that the correlation of phenetic distances with geographic distances were generally low and not significant, with the highest correlation occurring for finger-ridge counts, the lowest with mainline terminations and palm-ridge counts. If there are no correlations between phenetic and geographic distances, one would not expect spatial autocorrelation to be large or significant.…”
Section: Discussionmentioning
confidence: 49%
“…There appear to be no developmental factors causing high correlations between variables in different sets. In a study of correlation of distance matrices estimated from different categories of dermatoglyphic variables, Jantz et al (1992) found that most categories correlated only at a low level with other categories, but that finger patterns and finger counts were highly correlated, and palm patterns and mainline terminations were moderately correlated. Our present findings confirm these earlier results.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While there are many data about a-b ridge count (Floris and Sanna, 1982;Jantz and Webb, 1982;Pons, 1982), other palmar intertriradial ridge counts are relatively few (Jaeger, 1971;Knussmann, 1971;Hitzeroth and Brehme, 1974;Maté, 1975;Brehme et al, 1977;Dennis, 1977;Reichmann, 1978;Hitzeroth, 1979, 1980;Galaktionov et al, 1981;Gill et al, 1982;Babu, 1983;Gyenis, 1984;Karmakar and Malhotra, 1985;Hitzeroth et al, 1986;Jantz et al, 1988Jantz et al, -1992Brehme and Jantz, 1990;Arrieta et al, 1992;Marcellino, 1994-1995;Milicic and Rudan, 1991;Milicic and Vidovic, 2005;Reichmann, 1978;Deep Kumar and Ramachandraiah, 1991;Kamali, 1982;Reddy et al, 2004;Karmakar et al, 1996). The a-d ridge count in particular has been examined only in Asiatic populations (Basu, 1971;Chattopadhyay and Kushwaka, 1978;Balgir and Sharma, 1986;Narahari et al, 2008;Bhasin, 1970;Bansal et al, 1984;Chai, 1971), and in Sardinians (Floris, 1993;Floris and Sanciu, 1989), while data on persons from Bologna (Gualdi-Russo, 1987) from Galicia (Lodeiro Ainsua et al, 1985) and from Bulgaria (Tornjava-Randelov...…”
Section: Introductionmentioning
confidence: 99%